MiR-135 post-transcriptionally regulates FOXO1 expression and promotes cell proliferation in human malignant melanoma cells - Ren, Jian-Wen (Int J Clin Exp Pathol, 2015)
Malignant melanoma is the deadliest form of all skin cancers. Recently, microRNAs (miRNAs) are small, non-coding RNAs that regulate gene expression by targeted repression of transcription and translation and play essential roles during cancer development. Our study showed that miR-135a is upregulated in malignant melanoma tissues and cell lines by using Real-time PCR assay. Enforced expression of miR-135a in malignant melanoma cells promotes cell proliferation, tumorigenicity, and cell cycle progression, whereas inhibition of miR-135a reverses the function. Additionally, we demonstrated FOXO1 is a direct target of miR-135a and transcriptionally down-regulated by miR-135a. Ectopic expression of miR-135a led to downregulation of the FOXO1 protein, resulting in upregulation of Cyclin D1, and downregulation of P21(Cip1) and P27(Kip1) through AKT pathway. Our findings suggested that miR-135a represents a potential onco-miRNA and plays an important role in malignant melanoma progression by suppressing FOXO1 expression.